Methicillin Resistant Staphylococcus aureus (MRSA) Isolation and mecA Gene Detection from Milk and Farmer Hand Swab in Tulungagung, Indonesia - A. R. Khairullah; S. C. Kurniawan; O. S. M. Silaen; M. H. Effendi; S. A. Sudjarwo; S. C. Ramandinianto; M. A. Gololodo; A. Widodo; K. H. P. Riwu; D. A. Kurniawati; S. Rehman (Faculty of Animal Science, Bogor Agricultural University, 2023)
Staphylococcus aureus is a harmful bacterium that often contaminates milk; hence it is believed to become a severe health risk for humans. S. aureus resistant to β‑lactam drugs can be termed methicillin resistant Staphylococcus aureus (MRSA). Dairy farms have a high incidence of MRSA infections due to the repeated use of the same medicines on dairy cows and the physical contact between farmers and cows during milking. This study looked for MRSA in dairy cow milk and farmer hand swabs in Tulungagung, Indonesia. Using oxacillin and cefoxitin diffusion disks, phenotypic detection approaches were evaluated, then transferred to the Oxacillin Resistance Screening Agar Base (ORSAB) test and genotypically verified using PCR to find the mecA gene encoding MRSA. One hundred ten dairy cow milk samples and 45 farmer's hand swabs were collected from Tulungagung, East Java, Indonesia. Mannitol salt agar (MSA) was used for cultivation and purification. The disk-diffusion test used oxacillin and cefoxitin to identify S. aureus resistance. Oxacillin and cefoxitin-resistant S. aureus isolates were tested for MRSA using ORSAB. In addition, MRSA isolates were PCR-tested for the mecA gene. S. aureus was found in 110 (70.97%) of 155 isolates. Of the total 110 isolates of S. aureus, 16 (14.54%) and 39 (35.45%) were known to be resistant to Cefoxitin and Oxacillin, respectively. When tested with ORSAB, 23 isolates from 55 resistant isolates showed positive results for MRSA. Dairy milk was the source of most MRSA which is 15 isolates, while hand swabs only carried 8 isolates. However, PCR analysis only found mecA gene in two isolates. According to this study, many MRSA isolates were found from dairy farms in Tulungagung, Indonesia, but only a few have the mecA gene.